Comparison of UDM and CFD simulations of a time varying release of LPG in geometrical complex environment. (January 2017) - Gerbec, Marko; Pontiggia, Marco; Antonioni, Giacomo; Tugnoli, Alessandro; Cozzani, Valerio; Sbaouni, Mehdi; Lelong, Romain
Abstract: The paper discusses the release and air dispersion modelling for the specific potential accident scenario case of a vertical impinging jet of propane (below the sun shade/rain roof) out of an over-filled car tanker. The main purpose was to assess the related uncertainties in impact distances downwind to the Lower Flammability Limit (LFL) and half the LFL (LFL/2) propane concentrations in the ambient air, due to the proximity of the site border (issue of the control over the ignition sources). The conventional Unified Dispersion Modelling (UDM) results were re-modelled using a dynamic process simulation (to simulate the pressure safety release valve) and dispersion modelling using a Computational Fluid Dynamic (CFD) model simulation. The CFD model enabled explicit consideration of the 3D objects and impinging jet. The comparison of the impact distances down to LFL and LFL/2 concentrations among UDM and CFD models revealed that the CFD model suggests the distances are about 2-3 times shorter, but the fire hazard (propane-air mixture) is present for approximately twice the time after cessation of the propane release. This means that conventional UDM derived results using the integrated models are to some extent conservative, while on the other hand, the duration of the fire hazard is underestimated. The results are important for risk analysts in terms of the consideration of the use of the UDM models out of the validated contexts (e.g., vertical impinging, obstacles), as well as for site managers in considering whether the ignition prevention measures (separation distances) are sufficient. Graphical abstract: Highlights: Modelling of release & dispersion for vertical impingement of propane jet. Comparison of Unified Dispersion Modelling (UDM) and advanced CFD modelling. CFD model predicts comparatively 2–3 times shorter distances to LFL/2. CFD model considers vertical impingement and additional time needed for full dispersion. The duration of the fire hazard is under predicted by UDM.